Profile of Environmental Awareness and Environmental Care Attitude of Students at Junior High School 2 Kaliori, Rembang Regency - Fretty Anandita Normala; Irsadi, Andin; Ellianawati, Ellianawati (Unnes Science Education Journal, 2024)
The character of caring for the environment and environmental awareness in children occurs from school culture, cultivation and learning in the classroom. This makes a positive habit in children or students. The strengthening of the character of caring for the environment in students will make it a habit for children to become responsible human beings and care about the environment at school. This study aims to describe the environmental awareness profile and environmental care attitude in State Junior High School 2 Kaliori. The research method used in this study uses a quantitative approach with questionnaire data collection techniques. The analysis techniques used are validity tests, reliability tests and descriptive statistics. The results of the study obtained information that the level of environmental awareness at State Junior High School 2 Kaliori received an average score of 78.03 including the category of high environmental awareness. Meanwhile, the profile of the level of environmental care attitude at State Junior High School 2 Kaliori received an average score of 62.84 including the high category. The level of environmental concern attitude in State Junior High School 2 Kaliori in respondents with a high category of environmental concern attitude was 31 people or 68.9 percent and there were 14 respondents with a moderate level of environmental awareness or 31.1 percent. From the results of this research, there are several limitations of the research, namely only focusing on the profile of environmental care attitudes and environmental awareness of students of State Junior High School 2 Kaliori. As for the suggestions for the next researcher, it is hoped to add several other factors that affect environmental awareness and environmental awareness in schools. If there are other factors that affect environmental awareness and environmental awareness, of course, the results are also different, especially with different subjects.